Proceedings of the International Conference on Data Engineering and Communication Technology ICDECT 2016, Volume 1 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Joshi, Amit (Advances in Intelligent Systems and Computing,, 2017)
This two-volume book contains research work presented at the First International Conference on Data Engineering and Communication Technology (ICDECT) held during March 10-11, 2016 at Lavasa, Pune, Maharashtra, India. The book discusses recent research technologies and applications in the field of Computer Science, Electrical and Electronics Engineering. The aim of the Proceedings is to provide cutting-edge developments taking place in the field data engineering and communication technologies which will assist the researchers and practitioners from both academia as well as industry to advance their field of study.